The Relationship between Exclusive Breastfeeding and Diarrhea in Infant 6-12 Months - Ervyanna, Ellanda Rima; Salimo, Harsono; Kusnandar, - (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Diarrhea is the second leading cause of death in children under five in the world. It is a major cause of child morbidity and mortality in low- and middle-income countries. There are many risk and protective factors. One of the protective factors for diarrhea is exclusive breastfeeding. Breast milk contains antibodies that can protect babies from infectious diseases. This study aims to determine the relationship between exclusive breastfeeding and diarrhea in infants aged 6-12 months. Objective: This study used a crosssectional design. It involved a total of 171 infants selected using a simple random sampling technique. Data were collected using questionnaires related to exclusive breastfeeding and diarrhea. Data were analyzed using the Gamma correlation test with the help of IBM SPSS 24 software. Result: This study showed a relationship between exclusive breastfeeding and diarrhea (p= 0.000). Conclusion: There is a significant relationship between exclusive breastfeeding and diarrhea. The better the practice of exclusive breastfeeding, the better the immune system of the infant resulting in decreased diarrhea risks. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 377-382